A carbon quantum dot-modified high-conductive covalent organic framework composite material and preparation method thereof

By combining the conjugated structural carbon dots with covalent organic frame materials and avoiding structural damage through post-treatment process, a covalent organic frame composite material with high conductivity carbon quantum dot modification was prepared, which solved the problem of poor conductivity of existing COF materials, and achieved significant improvement in conductivity and optimization of battery performance.

CN118522864BActive Publication Date: 2025-04-15NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410723307.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-04-15
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

The existing covalent organic frame (COF) materials have poor electrical conductivity and are difficult to meet the requirements of battery applications. The combination of carbon quantum dots (CDs) and COF has problems with high structural damage and matching requirements.

Method used

By sonicating the quantum-sized conjugated structure carbon dots (CD) and covalent organic frame material (COF) in an organic solvent, a carbon quantum dot modified highly conductive covalent organic frame composite material (CD-COF) is prepared, and the influence of CD on the COF structure is avoided through a post-treatment process.

Benefits of technology

The conductivity of COF is improved, and the electron conductivity of CD-COF is significantly increased to 6.5×10-4S/cm, solving the problem of poor conductivity, while maintaining the advantages of COF's high specific surface area and charge storage site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118522864B_ABST
    Figure CN118522864B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon quantum dot-modified high-conductivity covalent organic framework composite material and a preparation method thereof, and belongs to the technical field of electrode materials. The preparation method of the carbon quantum dot-modified high-conductivity covalent organic framework composite material of the present invention comprises the following steps: adding quantum-sized conjugated structure carbon dots and covalent organic framework materials into an organic solvent, removing the organic solvent after ultrasonic treatment, and obtaining the carbon quantum dot-modified high-conductivity covalent organic framework composite material. The carbon quantum dot-modified high-conductivity covalent organic framework composite material prepared by the present invention not only inherits the advantages of high specific surface area and abundant charge storage sites of COF, but also makes up for its poor conductivity, and can be applied to the electrodes of batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a carbon quantum dot-modified high-conductivity covalent organic framework composite material and a preparation method thereof. Background Art

[0002] Electrode material design is the key to improving battery performance. The selection of electrode materials directly affects the energy density of the battery; the structure and composition of the electrode material determine the power output capacity of the battery; the chemical stability and structural stability of the electrode material are directly related to the safety of the battery. Therefore, the modification design of electrode materials is of great significance to the development of battery technology.

[0003] Covalent organic framework (COF) materials have a highly ordered porous structure, which can provide a large specific surface area, which is conducive to electrolyte penetration and ion transport; COF structure and composition can be customized through molecular design, which is very conducive to the introduction of highly active charge storage sites and the optimization of electrochemical performance; in addition, COF also has a highly covalently fixed network structure, which shows good chemical stability in electrochemical environments. However, the organic ligands of most COF materials lack a conjugated π bond system, which limits the effective transmission of electrons within the material, and the COF materials lack doping during the synthesis process, which cannot introduce enough carriers to improve the conductivity, which leads to the poor conductivity of many COF materials (generally less than 1×10 -6 S / cm), which is difficult to meet the requirements of battery applications.

[0004] Quantum-sized conjugated carbon dots (CDs) can form a conjugated system of electrons and promote the effective migration of electrons within the material; in addition, heteroatom doping can introduce additional carriers into CDs, thereby enhancing the overall conductivity of the material. Therefore, the prior art adds amino CDs to the COF precursor solution, utilizes the condensation of amino groups with aldehyde molecules in the COF precursor, and synthesizes the CD composite COF material in one step, utilizing the light absorption characteristics of CDs to improve the photoelectric conversion performance of the composite material, but CDs are embedded in the structural framework of COF. Due to the large difference in the size of CDs and the size of the precursor organic molecules in COF, CDs will seriously destroy the original framework structure of COF, affect the regularity and orderliness of COF, and weaken its original performance advantages. In addition, there are high requirements for the matching degree between the functional groups on the CD surface and the COF precursor molecules, and it does not have wide adaptability. How to prepare an electrode material with excellent performance has become a technical problem that technicians in this field need to solve urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon quantum dot-modified highly conductive covalent organic framework composite material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The carbon quantum dot-modified highly conductive covalent organic framework composite material of the present invention not only inherits the advantages of high specific surface area and abundant charge storage sites of COF, but also makes up for its poor conductivity defect, and can be applied to the electrode of the battery.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention: a method for preparing a carbon quantum dot-modified highly conductive covalent organic framework composite material, comprising the following steps:

[0008] The quantum-sized conjugated carbon dots and the covalent organic framework material are added into an organic solvent, and the organic solvent is removed after ultrasonic treatment to obtain the carbon quantum dot-modified high-conductivity covalent organic framework composite material.

[0009] Furthermore, the method for preparing the quantum-sized conjugated carbon dots comprises the following steps:

[0010] O-phenylenediamine and perchlorate are added into water, heated to dissolve, and then acid is added, and then a hydrothermal reaction is carried out to obtain the quantum-sized conjugated structure carbon dots.

[0011] Furthermore, the molar ratio of o-phenylenediamine to perchlorate is 1:1; the perchlorate includes sodium perchlorate; and the amount of the acid used is 5% of the total volume of water and the acid.

[0012] Furthermore, the temperature of the heating and dissolving is 80°C;

[0013] The temperature of the hydrothermal reaction is 200° C. and the time is 10 h.

[0014] Furthermore, the preparation method of the covalent organic framework material comprises the following steps:

[0015] 2,7-diaminopyrene-4,5,9,10-tetraone and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde are dispersed in a solvent, frozen and degassed under an inert atmosphere, and then sealed, followed by heat treatment to obtain the covalent organic framework material.

[0016] Further, the solvent comprises a mixed solution of mesitylene, 1,4-dioxane and acetic acid in a volume ratio of 9:3:1; the molar ratio of 2,7-diaminopyrene-4,5,9,10-tetraketone and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde is 3:2;

[0017] The concentration of the acetic acid is 6 mol / L.

[0018] Furthermore, the heat treatment is carried out at a temperature of 120° C. and for a period of 3 days.

[0019] Furthermore, the organic solvent includes ethanol; and the ultrasonic treatment time is 2 hours.

[0020] Furthermore, the method for removing the organic solvent includes heating evaporation; the temperature of the heating evaporation is ≤100°C.

[0021] The second technical solution of the present invention: a highly conductive covalent organic framework composite material modified with carbon quantum dots prepared by the above-mentioned preparation method.

[0022] The third technical solution of the present invention: Application of the above-mentioned carbon quantum dot-modified highly conductive covalent organic framework composite material in battery preparation.

[0023] The present invention discloses the following technical effects:

[0024] (1) The carbon quantum dot-modified highly conductive covalent organic framework composite material prepared by the present invention not only inherits the advantages of high specific surface area and abundant charge storage sites of COF, but also makes up for its defect of poor conductivity, and can be applied to the electrodes of batteries.

[0025] (2) The present invention synthesizes CD and COF separately, and then composites CD and COF through a post-treatment process, which effectively avoids the influence of CD on the original structure of COF. At the same time, there is no requirement for the CD surface structure to match the structure of the COF precursor molecule. It has the advantages of wide raw material adaptability and high synthesis controllability.

[0026] (3) The present invention effectively improves the conductivity of COF by compounding conjugated carbon quantum dots with COF. The electronic conductivity of the prepared carbon quantum dot-modified high-conductivity covalent organic framework composite material (CD-COF) is 6.5×10 - 4 S / cm, compared with the single COF material (2.1×10 -6 S / cm) has been significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a transmission electron microscope image of the CD prepared in Example 1 of the present invention;

[0029] Figure 2 This is a transmission electron microscopy image of the COF prepared in Example 1 of the present invention;

[0030] Figure 3 This is a transmission electron microscopy image of the CD-COF prepared in Example 1 of the present invention;

[0031] Figure 4 The electronic conductivity curves of COF and CD-COF prepared in Example 1 of the present invention are shown;

[0032] Figure 5 This is a transmission electron microscopy image of the CD-COF prepared in Comparative Example 2 of the present invention;

[0033] Figure 6 This is a transmission electron microscopy image of the CD-COF prepared in Comparative Example 3 of the present invention;

[0034] Figure 7 This is a structural simulation diagram of the COF prepared in Example 1 of the present invention;

[0035] Figure 8 Specific surface area diagram of COF and CD-COF prepared in Example 1 of the present invention;

[0036] Fig. 9 The charge and discharge curve of CD-COF prepared in Example 1 of the present invention;

[0037] Fig.10 The rate performance diagram of COF and CD-COF prepared in Example 1 of the present invention;

[0038] Fig.11 This is a cycle performance diagram of the CD-COF prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] Example 1

[0045] A method for preparing a highly conductive covalent organic framework composite material modified by carbon quantum dots:

[0046] (1) Preparation of CD: 1.081 g o-phenylenediamine (10 mmol) and 1.405 g NaClO4·H2O (10 mmol) were added to 19 mL of deionized water, stirred and heated at 80°C to dissolve, then 1 mL of 37 wt.% hydrochloric acid was added, transferred to a 50 mL polytetrafluoroethylene-lined reactor, and reacted at 200°C for 10 h. After the reaction was completed, the mixture was cooled to room temperature, the precipitate and the reaction solution were poured out, centrifuged at 4000 rpm for 5 min, the precipitate was washed twice with deionized water and n-butanol, respectively, and dried at 60°C overnight to obtain quantum-sized conjugated carbon dots (CD). The transmission electron microscopy image of CD is shown in Figure 1 .

[0047] from Figure 1 It can be seen that the CD size distribution is uniform and has an obvious lattice structure.

[0048] (2) Preparation of COF: 21.9 mg (0.075 mmol) of 2,7-diaminopyrene-4,5,9,10-tetraone and 19.67 mg (0.05 mmol) of 4,4',4"-(1,3,5-triazine-2,4,6-triyl) tribenzaldehyde were dispersed in 1.3 mL of a mixed solvent (the mixed solvent consisted of mesitylene, 1,4-dioxane, and 6 mol / L acetic acid in a volume ratio of 9:3:1), placed in a 10 mL Schlenk tube, and ultrasonically treated for 2 min to disperse the raw materials evenly. The mixture was then frozen and degassed three times under argon. The Schlenk tube was vacuum sealed and stored at 120°C for 3 days. After cooling to room temperature, the resulting black precipitate was separated by filtration, washed with methanol, tetrahydrofuran, and acetone, respectively, and then dried at 80°C in vacuum for 24 h to obtain a black powder, which was a covalent organic framework material (COF). The transmission electron microscopy image of COF is shown in FIG. Figure 2 .

[0049] from Figure 2 It can be seen that COF is a stacked structure with layers closely arranged.

[0050] (3) Preparation of CD-COF: 100 mg COF and 5 mg CD were added to 30 mL ethanol, ultrasonically treated for 2 h, and then heated at 80 °C until the solvent was completely evaporated to obtain a carbon quantum dot-modified highly conductive covalent organic framework composite material (CD-COF). The transmission electron microscopy image of CD-COF is shown in Figure 3 .

[0051] from Figure 3 It can be seen that the CD particles are successfully loaded into the COF layer structure, and the CD is evenly dispersed without obvious aggregation, which provides a good guarantee for the performance uniformity of the CD-COF composite material.

[0052] The electronic conductivity curves of COF and CD-COF under different pressures were tested by four-probe method. Figure 4 .

[0053] from Figure 4 It can be seen that the electronic conductivity of the CD-COF prepared in this example is 6.5×10 -4 S / cm, compared with the conductivity of COF (2.1×10 -6 S / cm) is significantly improved, indicating that the incorporation of CD enhances the electronic conduction of COF.

[0054] Comparative Example 1

[0055] One-step synthesis of COF composite carbon nanotubes:

[0056] 1,3,5-triformylphloroglucinol (10.5 mg, 0.05 mmol), 2,7-diamino-9,10-phenanthrenequinone (17.9 mg, 0.075 mmol), carbon nanotubes (10.0 mg), trimethylbenzene (0.9 mL), 1,4-dioxane (0.3 mL) and 3 mol / L acetic acid solution (0.1 mL) were mixed and loaded into a 10 mL Schlenk tube. The mixture was ultrasonically treated for 30 min, and three freeze pump-thaw cycles were performed, and vacuum was evacuated. The Schlenk tube was then sealed and placed in an oven at 120 ° C for 3 days. The black precipitate was collected by washing and filtering with DMF (3×5 mL), DMSO (3×5 mL) and acetone (3×5 mL) respectively. Finally, the solid was dried at 80 ° C in vacuum to obtain COF composite carbon nanotubes.

[0057] The conductivity of COF composite carbon nanotubes obtained by this method is 9.6×10 -5 S / cm, but because COF is deposited and stacked along the outer wall of carbon nanotubes, COF has a certain bending stress, which affects the layered structure of COF and results in fewer COF layers.

[0058] Comparative Example 2

[0059] Preparation method of CD-COF:

[0060] The same as Example 1, except that step (3) is specifically as follows: 100 mg COF and 5 mg CD are added to 30 mL ethanol, and heated and stirred at 80° C. for 2 h until the solvent is completely evaporated to obtain a carbon quantum dot-modified highly conductive covalent organic framework composite material (CD-COF). The transmission electron microscopy image of CD-COF is shown in Figure 5 .

[0061] from Figure 5 It can be seen that the CD particles are unevenly distributed and have a large size and some agglomeration.

[0062] Comparative Example 3

[0063] Preparation method of CD-COF:

[0064] The same as Example 1, except that step (3) is specifically as follows: 100 mg COF and 5 mg CD are added to 30 mL ethanol, and after ultrasonic treatment for 2 h, the solvent is completely evaporated at 120° C. to obtain a carbon quantum dot-modified highly conductive covalent organic framework composite material (CD-COF). The transmission electron microscopy image of CD-COF is shown in FIG. Figure 6 .

[0065] from Figure 6 It can be seen that when the solvent evaporation temperature is too high, CD will self-polymerize and no longer appear in a granular form.

[0066] Comparative Example 4

[0067] Preparation method of CD-COF:

[0068] (1) Preparation of CD: 1.081 g o-phenylenediamine (10 mmol) and 1.405 g NaClO4·H2O (10 mmol) were added to 19 mL of deionized water, stirred and heated at 80°C to dissolve, then 1 mL of 37 wt.% hydrochloric acid was added, transferred to a 50 mL polytetrafluoroethylene-lined reactor, and reacted at 200°C for 10 h. After the reaction was completed, the mixture was cooled to room temperature, the precipitate and the reaction solution were poured out, centrifuged at 4000 rpm for 5 min, and the precipitate was washed twice with deionized water and n-butanol, respectively, and dried at 60°C overnight to obtain quantum-sized conjugated carbon dots.

[0069] (2) Preparation of small-pore COF: 2,6-diaminoanthraquinone (DAAQ) (34 mg, 0.142 mmol), 2,4,6-triformylphloroglucinol (TFP) (20 mg, 0.096 mmol), N,N-dimethylacetamide (900 μL) and mesitylene (300 μL) were placed in a 10 mL Schlenk tube, and then 6 mol / L acetic acid (50 μL) was added to the mixture. The mixture was sonicated at room temperature for 1 min. Then three freeze-pump-thaw cycles were performed, and the tube was vacuumed, the Schlenk tube was sealed, and heated at 120 °C for 3 days. The resulting dark red precipitate was collected by filtration, washed with N,N-dimethylformamide (20 mL × 3), deionized water (20 mL × 3), and acetone (20 mL × 3), and the solid product was purified by acetone Soxhlet extraction for 12 h. The final product, small-pore COF, was obtained after vacuum drying at 120 °C for 12 h.

[0070] (3) Preparation of CD-COF: 100 mg COF and 5 mg CD were added to 30 mL ethanol, ultrasonicated for 2 h, and then heated at 80 °C until the solvent was completely evaporated to obtain a carbon quantum dot-modified highly conductive covalent organic framework composite material (CD-COF).

[0071] Since the pore size of the COF prepared in this comparative example is too small (2.2 nm) and does not match the average particle size of CD (2.6 nm), most CDs are loaded on the COF surface and are difficult to enter the COF pores, resulting in insufficient combination of CD and COF, and the conductivity is not significantly improved, about 7.8×10 -6 S / cm.

[0072] Effect Example 1

[0073] The structural simulation diagram of the COF prepared in Example 1 of the present invention is shown in Figure 7 .

[0074] from Figure 7 It can be seen that the pore size of the COF prepared in the example is 3.46 nm.

[0075] The specific surface area of ​​COF and CD-COF prepared in Example 1 of the present invention is shown in Figure 8 .

[0076] from Figure 8 It can be seen that the average pore size of COF is 3.38nm, which is close to the theoretical calculated value.

[0077] The charge-discharge curve of CD-COF prepared in Example 1 of the present invention at a current density of 0.1 A / g is shown in FIG. Fig. 9 .

[0078] from Fig. 9 It can be seen that the battery charge and discharge curves have high symmetry, indicating that the battery has good reversibility and exhibits a high specific capacity of 318 mAh / g.

[0079] The rate performance diagram of COF and CD-COF prepared in Example 1 of the present invention is shown in Fig.10 .

[0080] from Fig.10 It can be seen that compared with COF, the battery corresponding to CD-COF still has a high capacity retention rate at a current density of 10A / g. This is because CD doping improves the conductivity of COF, which in turn makes the corresponding battery have better rate performance.

[0081] The cycle performance diagram of CD-COF prepared in Example 1 of the present invention is shown in Fig.11 .

[0082] from Fig.11 It can be seen that at a current density of 5 A / g, the capacity of the CD-COF battery hardly decays after 5000 cycles of charge and discharge, indicating that it has good cycle stability.

[0083] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a highly conductive covalent organic framework composite material modified with carbon quantum dots for preparing battery electrodes, characterized in that: The following steps are involved: Adding quantum-sized conjugated carbon dots and covalent organic framework materials into an organic solvent, removing the organic solvent after ultrasonic treatment, and obtaining the carbon quantum dot-modified high-conductivity covalent organic framework composite material; The method for preparing the quantum-sized conjugated carbon dots comprises the following steps: Adding o-phenylenediamine and perchlorate into water, heating to dissolve, adding acid, and then performing a hydrothermal reaction to obtain the quantum-sized conjugated structure carbon dots; The preparation method of the covalent organic framework material comprises the following steps: 2,7-diaminopyrene-4,5,9,10-tetraketone and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde are dispersed in a solvent, frozen and degassed under an inert atmosphere, and then sealed, followed by heat treatment to obtain the covalent organic framework material; the solvent includes a mixed solution of mesitylene, 1,4-dioxane and acetic acid in a volume ratio of 9:3:1; the molar ratio of 2,7-diaminopyrene-4,5,9,10-tetraketone and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde is 3:2; the concentration of the acetic acid is 6 mol / L; the temperature of the heat treatment is 120°C and the time is 3 days; the organic solvent includes ethanol; and the time of the ultrasonic treatment is 2 hours.

2. The preparation method according to claim 1, characterized in that: The molar ratio of o-phenylenediamine to perchlorate is 1:1; the perchlorate includes sodium perchlorate; and the amount of the acid is 5% of the total volume of water and the acid.

3. The preparation method according to claim 1, characterized in that: The heating and dissolving temperature is 80°C; The temperature of the hydrothermal reaction is 200° C. and the time is 10 h.

4. A highly conductive covalent organic framework composite material modified with carbon quantum dots prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the carbon quantum dot-modified highly conductive covalent organic framework composite material according to claim 4 in battery preparation.

Citation Information

Patent Citations

  • Heteroatom-containing covalent organic framework electrode material and preparation method and application thereof

    CN111682207A

  • High-monochromaticity near-infrared fluorescent carbon dot as well as synthesis method and application thereof

    CN114605990A

  • Carbon quantum dot doped covalent triazine framework composite material as well as preparation method and application thereof

    CN115414966A

  • Preparation method of COFs iodine vapor electrochemical sensor based on oxidation-reduction activity

    CN116297696A